The Short-Run Residential Demand for Electricity - Barnes, Roberta; Gillingham, Robert; Hagemann, Robert (The Review of Economics and Statistics, 1981)
The model of short-run residential demand for electricity combines price-schedule information obtained from the Federal Energy Regulatory Commission with household-specific data from the 1972-73 Consumer Expenditure Survey to determine the household's level of electricity consumption and relate it to the household's demographic profile and appliance stock. The overall short-run price-elasticity estimate of -0.550 supports existing findings that short-run residential electricity demand is price inelastic. However, the variation in elasticities across end-use categories suggests that the overall response is made up of a complex set of responses that vary substantially and significantly across appliances. This implies that it may be more efficient to tailor conservation policies to the stock configuration of the population. 17 references, 6 tables.